Design thinking of character formation in basic training for prospective civil servants from the perspective of the qur'an - Neneng Maria Kiptyah (12 Waiheru, 2025)
This study formulates Design Thinking as a solution for character building for Prospective Civil Servants (CPNS). This study confirms that the Design Thinking approach can be applied in learning and compiling designs or actualization plans by following several stages in Design Thinking that focus on the formation of CPNS characters. The values contained in the Design Thinking stages are related to the Al-Qur’an because many Islamic spiritual values can be internalized in the Design Thinking stages. The method used in this study is qualitative research. The data obtained are based on library research, verses of the Al-Qur’an, publications in the form of books, research results, journals, conference or seminar proceedings, and articles. The study’s conclusion was obtained through a critical analysis of the decline in character of the younger generation, the generation that dominates the CPNS population. In addition, several steps were also applied to compile designs or actualization plans for CPNS Basic Training participants. By instilling character building from the beginning of Basic Training, CPNS is expected to grow into CPNS who are skilled and have high morals to serve the community. Thus, investment in CPNS character building will improve bureaucratic performance and increase public trust in the government. The recommendations given in this study to the government are to enhance character building for CPNS using design thinking applied in technical training, leadership training, and other training. Next, further activities are needed to implement Design Thinking insertion in CPNS competency development.